CONSUMER ACCEPTANCE AND ECONOMIC VALUE OF Cratoxylum formosum ESSENTIAL OIL - Muhamad Yusup Hidayat; Ridwan Fauzi; Grace Serepina Saragih; Alfonsus H. Harianja (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2023)
Cratoxylum formosum (Jack) Benth. & Hook.f. ex Dyer is one of the plant species that have the potential to be developed into an antibacterial and antioxidant essential oil product. This study was conducted to determine the value of organoleptic tests and the consumers' willingness to pay (WTP) for the three variants of Cratoxylum formosum essential oil products. For the parameters of colour, hedonic test values and score tests showed good results; panellists did not mind the pure and mixed Cratoxylum formosum essential oil colours. However, for fragrance parameters, the hedonic test showed a dislike score. Most panellists disliked the strong